Gender Roles in Nafsu Serakah (2019) Short Story through Appraisal Analysis - Yunita Nugraheni; Budi Tri Santosa (Universitas Muhammadiyah Semarang, 2022)
This article examines the gender roles expressed by the writer in Nafsu Serakah (2019) short story by Komala Sutha. The language used in Nafsu Serakah short story reveals how the writer point of view toward the difference roles between male and female. Therefore, Appraisal system developed by Martin and Rose (2003) is used to analyze the clauses found in Nafsu Serakah (2019) short story. There are 69 clauses found in Nafsu Serakah (2019) short story that reveal the writer’s point of view toward the difference roles between male and female. In short way, the male character is described more positive than the female character.